AN EXPERIMENTAL STUDY EVALUATING THE INFLUENCE OF QUERCETIN ON MONOSODIUM GLUTAMATE-INDUCED DEPRESSION IN SWISS ALBINO MALE MICE - SRIRAM BS; RAVICHANDRA V (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to evaluate the antidepressant activity of quercetin in monosodium glutamate (MSG) model of depressed male mice. Methods: MSG was administered (500 mg/kg) to different groups of albino male mice daily for 21 days to induce depression. The interventions (Quercetin and imipramine) were started on day 9th and continued till 21st day. On 23rd day, mice are sacrificed, hippocampus and amygdala supernatant are subjected for analysis. p<0.05 was considered as statistically significant. Results: There was a statistically significant reduction in interleukin (IL)-6 levels in animals treated with quercetin and imipramine compared to control group (p<0.001). There was also a statistically significant increase in brain-derived neurotrophic factor (BDNF) levels in quercetin with MSG groups (p<0.05) and imipramine with MSG groups (p<0.01). There was no statistically significant difference in IL-6 and BDNF levels between the groups of animals treated with quercetin (100 mg/kg) and imipramine (10 mg/kg) alone. Conclusion: Quercetin appeared to have an antidepressant activity. More extensive research is required to substantiate and elucidate the role of quercetin in behavioral disorders such as depression.